2013
DOI: 10.1371/journal.pone.0079971
|View full text |Cite
|
Sign up to set email alerts
|

Production of the First Effective Hyperimmune Equine Serum Antivenom against Africanized Bees

Abstract: Victims of massive bee attacks become extremely ill, presenting symptoms ranging from dizziness and headache to acute renal failure and multiple organ failure that can lead to death. Previous attempts to develop specific antivenom to treat these victims have been unsuccessful. We herein report a F(ab)´2-based antivenom raised in horse as a potential new treatment for victims of multiple bee stings. The final product contains high specific IgG titers and is effective in neutralizing toxic effects, such as hemol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Despite the low number of deaths, the accident with bees is still a concern, as it may often be a case of a medical emergency. Also, since antivenom is undergoing clinical trials, severe cases have only been treated with clinical support 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the low number of deaths, the accident with bees is still a concern, as it may often be a case of a medical emergency. Also, since antivenom is undergoing clinical trials, severe cases have only been treated with clinical support 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , the hemolytic activity of 1 mg of bee venom was neutralized by ~50 mg of the antivenom. In vivo , the horse antivenom was able to completely neutralize the myotoxic effects of bee venom with an effective dose (ED 50 ) of 1.11 mg/mL (mg of bee venom/mL of antivenom) (180). Also, using horse immunization, Barraviera and co-authors recently developed a horse F(ab') 2 -based antivenom with an ED 50 of 1.25 mg/mL (181).…”
Section: Next-generation Antivenom Therapymentioning
confidence: 99%
“…The PE + CVVHDF combination also reduced A definitive treatment for venom-induced MODS has not been established yet. Many therapeutic procedures, including specific honey bee anti-venom, adrenaline, hydrocortisone, optimal hydration and alkaline diuresis, have been evaluated and found to have limited benefits [13,14] . However, only a few studies have reported the use of blood purification for venom-induced MODS treatment.…”
Section: Discussionmentioning
confidence: 99%